Influence of surfactant on ZnO varistors - Dhage, S. R.; Navale, S. C.; Ravi, V. (Ceramics International, 2007)
ZnO varistors with and without surfactant such as sodium dodecyl sulphate (SIDS) are prepared by nitrate-combustion process. The samples were identically heat treated and sintered at 1000 degrees C for 12 h to study the influence of the surfactant on the nonlinear electrical properties of polycrystalline ZnO. It is observed that the nonlinear coefficient decreases marginally (alpha = 35) for samples prepared with surfactant, whereas breakdown field (E-B = 130 V/mm) decreased significantly. The corresponding parameters for the samples synthesized without surfactant are alpha = 45 and E-B = 400 V/mm. Hence, this method can be used for the manufacture of varistors with low to moderate breakdown fields. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Chemical synthesis; Semiconductors; X-ray methods; ZnO